Clay Ingestion During Pregnancy Among Black African Women in a North London Borough: Understanding Cultural Meanings, Integrating Indigenous and Biomedical Knowledge Systems - Madziva, Cathrine; Chinouya, Martha Judith (Frontiers in Sociology, 2020)
Findings from this qualitative audit conducted in a North London Borough among Black African women show that clay ingestion during pregnancy is a cultural phenomenon embedded in indigenous knowledge (IK). Reasons for clay ingestion include curbing morning sickness, nausea, satisfying cravings, “mineral deficiency” and other life sustaining beliefs. However, Public Health practitioners' top down approach and response which considers the practice as “dangerous” and potentially harmful to the health of the woman and unborn child with midwives and General Practitioner doctors called upon to discourage it, risks alienating the target population. Furthermore, within such a top down framework, opportunities to integrate biomedical science and indigenous knowledge systems are potentially missed. The use of culturally sensitive Public health interventions which consider a community approach, while attempting to integrate these two knowledge systems through further research is likely to bear more fruits.